2022
DOI: 10.1161/jaha.121.023322
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Clearance as a Surrogate for Mortality in Cardiogenic Shock: Insights From the DOREMI Trial

Abstract: Background Recent studies have shown improved outcomes in cardiogenic shock through protocols directed toward early identification and initiation of mechanical circulatory support. However, objective therapeutic targets—based on clinical and/or laboratory data—to guide real‐time clinical decision making are lacking. Lactate clearance has been suggested as a potential treatment target because of its independent association with mortality. Methods and Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 30 publications
(33 reference statements)
1
17
0
Order By: Relevance
“…A recent meta-analysis found that, among an allcomers CS cohort, survivors had significantly greater lactate clearance at 6–8 and 24-h compared to nonsurvivors [25]. Similar results were found in a substudy of the DOREMI trial, where there was a greater rate of lactate normalization among survivors than nonsurvivors at all timepoints, including as early as 4-h from randomization [26 ▪▪ ].…”
Section: Laboratory Parameterssupporting
confidence: 52%
“…A recent meta-analysis found that, among an allcomers CS cohort, survivors had significantly greater lactate clearance at 6–8 and 24-h compared to nonsurvivors [25]. Similar results were found in a substudy of the DOREMI trial, where there was a greater rate of lactate normalization among survivors than nonsurvivors at all timepoints, including as early as 4-h from randomization [26 ▪▪ ].…”
Section: Laboratory Parameterssupporting
confidence: 52%
“…The systemic review of 12 studies analyzing the association between lactate clearance and outcomes in patients with CS showed that survivors had 17.3% higher level of lactate clearance at 6–8 h ( p < 0.001) and 27.9% higher level of lactate clearance at 24 h ( p < 0.001) compared to non-survivors [ 39 ]. In a randomized, double-blind, controlled DOREMI (Dobutamine Compared to Milrinone in the Treatment of Cardiogenic Shock) prospective trial, lactate clearance was a significant survival predictor at all time points, with OR between 2.46 at 8 h (95% CI 1.09–5.55; p = 0.03) to 5.44 at 24 h (95% CI 2.14–13.8; p < 0.01) [ 40 ]. The possible pathologic mechanisms of the above mentioned association was investigated in the recent Cardiac Magnetic Resonance Imaging Study in 360 patients with AMI undergoing PCI, where the levels of admission lactate above 2.5 mmol/L showed a higher association with a larger size of myocardial injury (OR 1.59; 95% CI 1.00–2.51; p = 0.048) [ 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, most monitoring tools are indirectly re ecting the status of microcirculation (e.g. the Mottling score [5,25], skin temperature [26], central-to-toe temperature difference [4,26], lactate and lactate clearance [27], peripheral perfusion index [28], etc.). Thirdly, the accuracy remains to be proven.…”
Section: Discussionmentioning
confidence: 99%